Controversies in the Management and Followup of Differentiated Thyroid Cancer: Beyond the Guidelines. (30th December 2012) - Ahmadieh, Hala; Azar, Sami T.
Abstract : Thyroid cancer is among the most common endocrine malignancies. Genetic and environmental factors play an important role in the pathogenesis of differentiated thyroid cancer. Both have good prognosis but with frequent recurrences. Cancer staging is an essential prognostic part of cancer management. There are multiple controversies in the management and followup of differentiated thyroid cancer. Debate still exists with regard to the optimal surgical approach but trends toward a more conservative approach, such as lobectomy, are being more favored, especially in papillary thyroid cancer, of tumor sizes less than 4 cm, in the absence of other high-risk suggestive features. Survival of patients with well-differentiated thyroid cancer was adversely affected by lymph node metastases. Prophylactic central LN dissection did improve accuracy in staging and decrease postop TG level, but it had no effect on small-sized tumors. Conservative approach was more applied with regard to the need and dose of radioiodine given postoperatively. There have been several advancements in the management of radioiodine resistant advanced differentiated thyroid cancers. Appropriate followup is required based on risk stratification of patients postoperatively. Many studies are still ongoing in order to reach the optimal management and followup of differentiated thyroid cancer.